The battle for the banks - May, A. L. (Sydney ; London : Methuen, 1968)
This book includes relationship of the bank nationalization move have to the later split in the labor party.
"Banking Act, 1947": p. 145-174.
Includes the Fabian Society's booklet The case for bank nationalism.
Bibliography: p. 218-224.
MF22/01/2019
Loans
Keywords: Banks and banking; Australia